Muhammed Esad dede ve mesnevi şerhi - Öktay, Nesrin (My University, 2008)
Muhammed Esad Dede 19. asrın sonları ile 20. asrın başlarında yaşamış mutasavvıf bir şahsiyettir. 1843 yılında Selanik’te doğan Esad Dede, ilk öğrenimini burada tamamladıktan sonra İstanbul’a gelmiş, ileri derecede Arapça ve Farsça öğrenmiştir. Pek çok hocadan özel dersler ve bir çok tarikatten icâzet almıştır. Hayatının son yıllarında mesnevîhanlık görevini ifâ etmiş, yazdığı pek çok eseri Yenikapı Mevlevihanesi’nde yanarak yok olmuştur. Günümüze ulaştığını bildiğimiz iki eseri bulunmaktadır. Bunlar, İmdadullah Tehânevî’nin Ziyau’l-kulûb adlı eserinin tercümesi ve Şerh-i Mesnevî’dir. Şerh-i Mesnevî’de Esad Dede, Mesnevî’nin 500 küsür beytini çeşitli mutasavvıfların görüşlerinden hareketle ve mensur olarak şerh etmiştir. Bu çalışmada önce Mesnevî tercüme ve şerhleri hakkında bilgi verilmiş, ardından Esad Dede’nin hayatı, ilmî-edebî-tasavvufî şahsiyeti incelenmiştir. Şerh-i Mesnevî’nin Konya’da bulunan iki nüshası karşılaştırılmış ve sağlam bir metin elde edilmeye çalışılmıştır

Muhammed Esad Dede who is a guru lived between at the end of 19. Century and at the beginning of 20. Century. Esad Dede was born in Selanik in 1843. After he completed his basic education in Selanik, came Istanbul and learned advanced level of Persian and Arabic languages. He got private lessons from many teachers and authorization from many sects. In the last years of his life, he became mesnevihân. Texts written by Esad Dede were consumed because of a fire in Yenikapı Whirling Dervish Hall. At present we have two extant text of Esad Dede. These are: “The Translation of Ziya’ul-kulûb which belongs to İmdadullah Tehanevi” and “Şerh-i Mesnevî”. In Commentary of Mesnevî, Esad Dede explained almost 500 verse of Mesnevî. His explanation is based on different gurus’ thought. In this work, firstly the information about translation and commentary of Mesnevî are given and then life of Esad Dede and his technical, literary and sufistic character are analysed. The two copy of the Commentary of Mesnevî in Konya are collated and it was tried to obtain correct text. Key Words: Esad Dede, 18. Century, Sufism, Mesnevî, Commentary.
Keywords: İslam Dini; İslam Tairihi; Mesnevi